Crank-Nicolson finite difference method for two-dimensional fractional sub-diffusion equation - Ali, Umair; Abdullah, Farah Aini; Ismail, Ahmad Izani (International Scientific Publications and Consulting Services (ISPACS), 2017)
A Crank-Nicolson finite difference method is presented to solve the time fractional two-dimensional sub-diffusion equation in the case where the Gr¨unwald-Letnikov definition is used for the time-fractional derivative. The stability and convergence of the proposed Crank-Nicolson scheme are also analyzed. Finally, numerical examples are presented to test that the numerical scheme is accurate and feasible.